Ethics after poststructuralism : a critical reader - Olsen, Lee, 1984-; Johnston, Brendan, 1981-; Keniston, Ann, 1961- (Jefferson, North Carolina : McFarland & Company, Inc., 2020)
"In an era of economic devastation, ongoing legacies of colonization and imperialism, climate change and habitat loss, there is a call for a new understanding of the meaning and relevance of ethics. These essays on otherness, responsibility, and hospitality raise urgent questions about the state of ethics in tumultuous times. Contributors range from prominent theorists-including Levinas, Michel Foucault, Jacques Derrida, and Giorgio Agamben-to more recent theorists including Judith Butler, Enrique Dussell, and Rosi Braidotti. Perhaps most crucially, this reader emphasizes the always vulnerable status of a radically different Other, even as it questions what responsibility to that Other might mean."--Provided by publisher"--
Includes bibliographical references and index.
Keywords: Ethics -- History -- 20th century; Ethics, Modern -- 20th century; Ethics -- History -- 21st century; Ethics, Modern -- 21st century; Poststructuralism